On the issue of the current state of agriculture of the Kazakhstan - Beisengaliyev B.Т.; Kozhabaeva S.А.; Turekulova D.М.; Zhanybayeva Z.К. (BUKETOV BUSINESS REVIEW, 2021)
Object: analysis and assessment of the state of poultry farming (including determining the dynamics of the poultry industry development) in the leading regions of Kazakhstan Methods: In particular, the study comparative, logistic, specific methods of analysis are used: economicmathematical, economic-statistical; graphical interpretation of information, an experimental method that includes conducting a ascertaining experiment, analyzing and summarizing the data obtained, which made it possible to assess the state and development of the main sub-sectors of agriculture, revealed the leading regions of Kazakhstan in the development of poultry farming. Findings: A comprehensive analysis of crop and poultry production in Kazakhstan is conducted. In particular, the dynamics of the development of the poultry sector for the period from 2010 to 2019, the number of birds in regions of Kazakhstan were studied. Conclusions: The agricultural sector is a key sector of the economy of Kazakhstan, so the degree of its development affects the provision of food security, as well as the socio-political stability of the state. To meet domestic needs it is necessary to develop poultry farming, thereby reducing import dependence in a number of poultry products. Consequently, the complex reasons for the decline in the number of birds by region are determined, measures are proposed to minimize the impact of restraining factors in the development of poultry farming.